Growth in Skull Length and Width of the Arctic Wolf: Comparison of Models and Ontogeny of Sexual Size Dimorphism - Larter, Nicholas C.; Nagy, John A.; Bartareau, Tad M. (ARCTIC, 2012)
We compared four classical nonlinear growth curves (Gompertz, Logistic, Richards, and von Bertalanffy) in modeling observed skull condylobasal length and zygomatic width as a function of age in wild arctic wolves (Canis lupus arctos). We analyzed gender-specific growth patterns and the ontogeny of sexual size dimorphism in this species as revealed by the best model from these alternatives. For both genders and skull size measurements, the size-at-age data provided the best support for the von Bertalanffy model because of higher fitting degrees, lower root mean squared standard deviation of data points about the fitted growth curve, Akaike weight of 37.4% or higher, and fewer parameters derived directly from metabolic laws. Male asymptotic condylobasal length was 3.2% longer, and zygomatic width 4.1% wider, than in females. Sexual size dimorphism in this species develops in part because males grow faster, which might benefit them in terms of reproductive success and the capture and killing of large ungulate prey. Nous avons comparé quatre courbes de croissance non linéaires classiques (Gompertz, logistique, Richards et von Bertalanffy) se rapportant à la modélisation de la longueur condylobasale de crânes observés et à leur largeur zygomatique en fonction de l’âge chez les loups arctiques sauvages (Canis lupus arctos). Ensuite, nous avons analysé les tendances de croissance en fonction de la sexospécificité et de l’ontogenèse de dimorphisme sexuel chez cette espèce, tel que révélé par le meilleur de ces modèles. Dans le cas des données relatives au sexe et aux mesures de tailles de crânes, les données propres aux tailles selon l’âge ont fourni le meilleur support pour le modèle de von Bertalanffy en raison de degrés de raccord plus élevés, d’un écart-type moyen inférieur des points de données sur la courbe de croissance ajustée, d’un poids Akaike de ≥ 37,4 % et de moins de paramètres directement dérivés des lois métaboliques. La longueur condylobasale asymptotique du mâle était de 3,2 % plus prononcée et sa ...